In vitro degradation and in vivo biocompatibility of chitosan-poly(butylene succinate) fiber mesh scaffolds - Pinto, A. R. (2014)
In tissue engineering, the evaluation of the host response to the biomaterial implantation must be assessed to determine the extent of the inflammatory reaction. We studied the degradation of poly(butylene succinate) and chitosan in vitro using lipase and lysozyme enzymes, respectively. The subcutaneous implantation of the scaffolds was performed to assess tissue response. The type of inflammatory cells present in the surrounding tissue, as well as within the scaffold, was determined histologically and by immunohistochemistry. In the presence of lipase or lysozyme, the water uptake of the scaffolds increased. Based on the weight loss data and scanning electron microscopy analysis, the lysozyme combined with lipase had a notable effect on the in vitro degradation of the scaffolds. The in vivo implantation showed a normal inflammatory response, with presence of neutrophils, in a first stage, and macrophages, lymphocytes, and giant cells in a later stage. Vascularization in the surrounding tissue and within the implant increased with time. Moreover, the collagen deposition increased with time inside the implant. In vivo, the scaffolds maintained the structural integrity. The degradation in vitro was faster and greater compared to that observed in vivo within the same time periods.